(untitled) (Вісник: Міжнародні відносини, 2024)
The paper is devoted to analysis of the EU cohesion policy, assessment of its elaboration and implementation to decrease regional disproportions in the EU member states and regions. There is a focus on modern instruments of assistance under the pandemic as a reaction to social and economic challenges. The cohesion reports of the European Commission are discussed. Econometric analysis provided an evidence for efficiency of the cohesion policy at the NUTS-2 and NUTS-1 regions level. Conclusions on its effects on economic structure and development of the regions are provided. The most vulnerable types of regions and industries are determined. Assistance from the European structural and investment funds in some areas was stabilizing instrument, which smoothed recession under the pandemic.